Correlation between structural and transport properties of electron beam irradiated PrMnO3 compounds. (February 2018) - Christopher, Benedict; Rao, Ashok; Nagaraja, B.S.; Shyam Prasad, K.; Okram, G.S.; Sanjeev, Ganesh; Petwal, Vikash Chandra; Verma, Vijay Pal; Dwivedi, Jishnu; Poornesh, P.
Abstract: The structural, electrical, magnetic, and thermal properties of electron beam ( EB ) irradiated PrMnO3 manganites were investigated in the present communication. X-ray diffraction data reveals that all samples are single phased with orthorhombic distorted structure ( Pbnm ). Furthermore, the diffracted data are analyzed in detail using Rietveld refinement technique. It is observed that the EB dosage feebly disturbs the MnO6 octahedra. The electrical resistivity of all the samples exhibits semiconducting behavior. Small polaron hopping model is conveniently employed to investigate the semiconducting nature of the pristine as well as EB irradiated samples. The Seebeck coefficient ( S ) of the pristine as well as the irradiated samples exhibit large positive values at lower temperatures, signifying holes as the dominant charge carriers. The analysis of Seebeck coefficient data confirms that the small polaron hopping mechanism assists the thermoelectric transport property in the high temperature region. The magnetic measurements confirm the existence of paramagnetic ( PM ) to ferromagnetic ( FM ) behavior for the pristine and irradiated samples. In the lower temperature regime, coexistence of FM clusters and AFM matrix is dominating. Thus, the complex magnetic behavior of the compound has been explained in terms of rearrangement of antiferromagnetically coupled ionic moments. Highlights: Small polaron hopping model is valid for pristine and irradiated samples. Magnetic measurements show existence strong paramagnetic behavior at higher temperatures. Large Seebeck coefficient is observed for pristine and irradiated samples.